2020
DOI: 10.1097/fbp.0000000000000535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antidepressive property of β-hydroxybutyrate in mice

Abstract: β-hydroxybutyrate, a ketone body metabolite, has been shown to suppress depression-like behavior in rodents. In this study, we examined its antidepressive property in acute and chronic administration modes in mice by using forced swim test and tail suspension test. Results showed that the decrease effect of β-hydroxybutyrate (300 mg/kg) on immobility time in the tail suspension test and forced swim test in stress-naive mice began to be significant at day 11. In a dose-dependent experiment, β-hydroxybutyrate tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“…The BHB is one of the ketone bodies converted from fats and fatty acids. It has been recently reported that BHB induces BDNF expression in cortical neurons, 40 inhibits hippocampal neuroinflammation, 14 and has an antidepressant‐like behavioral effect 14,15 . In this study, acute injection of low‐dose C10 produced no significant differences in plasma BHB levels between treatment groups.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…The BHB is one of the ketone bodies converted from fats and fatty acids. It has been recently reported that BHB induces BDNF expression in cortical neurons, 40 inhibits hippocampal neuroinflammation, 14 and has an antidepressant‐like behavioral effect 14,15 . In this study, acute injection of low‐dose C10 produced no significant differences in plasma BHB levels between treatment groups.…”
Section: Discussioncontrasting
confidence: 44%
“…It has been recently reported that BHB induces BDNF expression in cortical neurons, 40 inhibits hippocampal neuroinflammation, 14 and has an antidepressant-like behavioral effect. 14,15 In this study, acute injection of low-dose C10 produced no significant differences in plasma BHB levels between treatment groups. Our results showed that the acute behavioral effects of low-dose C10 were not associated with plasma BHB levels.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Furthermore, endogenous NLRP3 inhibition by d-3HB alleviated stress-induced anxiety and post-traumatic stress disorder (PTSD) (Yamanashi et al 2017(Yamanashi et al , 2020. d-3HB also promoted the effect of a subtherapeutic dose of an anti-depressant drug, which led to suppression of chronic unpredictable stress-induced increase in immobility time and reduction in body weight in rat studies (Pan et al 2020).…”
Section: D-3hb and Brain Healthmentioning
confidence: 99%